Effect of adjustable gastric banding on quality of life and weight loss in the Helping Evaluate Reduction in Obesity (HERO) registry study: 2 year analysis. (3rd August 2015) - Lao, W.-L.; Malone, D.C.; Armstrong, E.P.; Voellinger, D.; Somers, S.; Jin, J.; Dreyer, N.; Globe, D.
Abstract: Objective: This report from the Helping Evaluate Reduction in Obesity (HERO) Study investigated weight loss, health-related quality of life (HRQOL), and factors predictive of HRQOL improvement during a 2 year period following Lap-Band AP * implantation (post-LBAP). Research design and methods: This prospective, observational study included patients with 1 and 2 year follow-up data post-LBAP ( N = 585). Changes in body mass index (BMI), percentage of weight loss (%WL), excess weight loss (%EWL) and HRQOL (Impact of Weight on Quality of Life [IWQOL]–Lite measure), and differences between <30% EWL and ≥30% EWL subgroups were assessed at 1 and 2 years post-LBAP. Multiple linear regression examined association of %EWL groups with IWQOL-Lite scores controlling for age, gender, region (US vs outside US), household income, employment status, and comorbidities. Results: Most patients were female (80.2%) and from the US (64.8%); overall mean (SD) age was 43.6 (11.28) years and 65.8% of patients had ≥30% EWL at year 2. At 2 years post-LBAP, mean %EWL was 43.5%; %EWL was 12.4% in the <30% EWL group and 59.6% in ≥30% EWL group ( P ≤ 0.0001). Changes in IWQOL total and subscores were significantly greater in ≥30% EWL versus <30% EWL patients (all P < 0.0005) at years 1 and 2; Self-Esteem and Physical subscores had the largest changes. Multiple regression analysis showed that patients with ≥30% EWL had clinically meaningful improvements in HRQOL compared with patients having <30% EWL ( P ≤ 0.001). Similarly, US patients and females had a clinically significant change in IWQOL score versus their counterparts ( P ≤ 0.001). Conversely, income, comorbidities and employment status were not significant predictors of change in IWQOL scores at year 2. Conclusions: These results support and extend findings regarding the effectiveness of LBAP for weight loss and illustrate the importance of ≥30% EWL as a significant factor in predicting clinically significant improvement in HRQOL 1 and 2 years post-LBAP. Clinical trial registration: NCT00953173.